Performance study of differential frequency hopping - Balaguru Ramkumar (2016)
Differential frequency hopping (DFH) is a variant o f frequency-hopping system. The variation lies in the construction of frequency-transition function. In a DFH system, the frequency transition depends on the previous hop and current input unlike the fast frequency-hopping (FFH) system where a pseudo-random generator is used to determine the frequency hop. Also, there is no need for synchronization between the transmitter and receiver. This report presents the study of the DFH system in additive white Gaussian noise environments. Also, the BER performance of binary frequency-shift keying (BFSK), FFH/BFSK is also studied which provides the basic understanding for the study of frequency hopping systems and aides in the study of DFH systems. The performance of the DFH system in a Rayleigh-fading environment is also studied. BER curves are obtained for different DFH systems by constructing different generator structures. The DFH system shows superior performance than the FFH/BFSK system. The performance of DFH systems is almost the same for higher rate encoder structures, based on state trellis, which shows that a lower-order encoder structure with less complexity can be used for a given application. Finally, the impact of constraint length of the generator on the encoder structure is also studied.